Defamation of Family Reputation on Social Media According to Positive Law and Islamic Law: A Case Study at Ternate Police Department - Fara, Yudi; Abbas, Abdul Haris; Husein, Muhammad AR. (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the handling of family defamation cases on social media from the perspectives of positive law and Islamic law, using a case study at the Ternate Police Department. The increasing number of cases over the past five years indicates that social media has become a new arena for conflict, significantly affecting family reputation. This research employs a qualitative approach with a juridical-empirical method. Data collection techniques include observation, in-depth interviews, documentation, and literature review. The findings reveal that the Ternate Police adopt a combination of litigative approaches based on the Electronic Information and Transactions Law (ITE Law) and the Indonesian Penal Code (KUHP), alongside non-litigative approaches through restorative justice mechanisms. From the Islamic law perspective, defamation is seen as a violation of ḥifẓ al-ʿirḍ (protection of dignity), which can be resolved through principles such as iṣlāḥ (reconciliation) and social repentance. The application of criminological theories—strain, differential association, broken windows, and deterrence—strengthens the understanding of offender motives and patterns of deviance in digital spaces. In conclusion, addressing family defamation requires an integrative approach that combines legal enforcement, Islamic ethical principles, and adaptive social responses to digital-era challenges.